UJI PENDAHULUAN PENGGUNAAN TEPUNG DAUN SEREH (Andropogon nardus) DAN DRINGO (Acorus calamus) TERHADAP MORTALITAS Sitophilus zeamais (Motschulsky) (COLEOPTERA; CURCULIONIDAE) PADA BIJI JAGUNG DI PENYIMPANAN - Khasanah, Nur (AgriSains, 2009)
The research aimed to determine sereh (Andropogon nardus) and dringo (Acorus calamus) leaf mash effects on the mortality of Sitophilus zeamais in storage corn seeds. The study used a Completely Randomized Block design with three replicates. The treatments consisted of 1 g sereh and dringo leaf mash, 2 g sereh and dringo leaf mash, 3 g sereh and dringo leaf mash, 4 g sereh and dringo leaf mash, 5 g sereh and dringo leaf mash, and control. The research results indicated that even at the lowest dosage (1 g sereh and dringo leaf mash), the mortality of the tested S. zeamais was quite high (22.50%).Key words : Sitophilus zeamais, sereh (Andropogon nardus), dringo (Acorus calamus)